Analysis of the Teman Bus Service (Trans Metro Dewata) at the Domestic and International Arrival Terminals of I Gusti Ngurah Rai Airport - Ayu PutriSri Undari Dewi; Ida Ayu Putu Sri Widnyani; I Wayan Astawa (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Abstract Public transportation or public transportation is one of the government's efforts to overcome the problem of congestion which often experiences obstacles and problems and is supported by the development of tourism in Bali so that it requires efforts in the field of transportation, especially in the area of ​​I Gusti Ngurah Rai Airport. So the government implemented it in an application-based public transportation service called Teman Bus which in its implementation is still considered inefficient. This study uses a qualitative method using the Servqual theory) with 10 dimensions in determining service quality, namely: Access, Communication, Competence, Courtesy, Credibility, Reliability, Responsiveness, Security, Tangibles, Understanding / Knowing the Customer. The results of this study indicate that the quality of Teman Bus services at I Gusti Ngurah Rai Airport needs to be improved because it has not been running optimally. The factors that are obstacles in Teman Bus services at I Gusti Ngurah Rai Airport are the lack of participation and support from the central and regional governments, the lack of socialization of Teman Bus services to the community, and the lack of public interest in using Teman Bus public transportation. Keywords: Service Quality, Public Transportation, Teman Bus, Efficiency, Application Based Services